Mechanism and realization path of new quality productivity enabling modern marine industrial system - Chen, Xiaolong; Di, Qianbin; Wang, Zhen (Frontiers in Marine Science, 2025)
New quality productivity (NQP) has infused fresh impetus into the construction and development of the modern marine industrial system (MMI), becoming a pivotal force in driving the high-quality development of the marine economy. This paper elucidates the value implications of NQP in fostering the formation and expansion of the MMI. By clarifying the internal mechanisms of this system, we delineate the goal orientation of the MMI enabled by NQP. We conduct an in-depth exploration of the enabling process of the MMI across five dimensions: innovation-driven growth, factor matching, integrated development, supply-demand adaptation, and green and low-carbon practices. The paper highlights that leveraging NQP can unlock the potential of traditional industries, strategically position emerging and future industries, enhance the impetus for innovation in marine science and technology, optimize the environment for marine industry development, accelerate industrial and digital integration, and improve policies related to green industries, technologies, and sustainable development. These measures aim to further implement the maritime power strategy and promote the empowerment and enhancement of the high-quality development of the marine economy.